ChemInform Abstract: NH‐Heterocyclic Aryliodonium Salts and Their Selective Conversion into N1‐Aryl‐5‐iodoimidazoles. Issue 42 (September 2016) - Wu, Yichen; Izquierdo, Susana; Vidossich, Pietro; Lledos, Agusti; Shafir, Alexandr
Abstract: New (NH‐imidazolyl)aryl iodonium acetates can be easily prepared from imidazole and aryliodonium diacetates and their Cu(II)‐catalyzed rearrangement is studied to provide a synthesis of N1‐aryl‐5‐iodoimidazoles.